Families with Intellectual Disability Members: The Kind of Perceived Parents’ Needs - Ioannis, Paxinos; Chaldi, Dimitra; Konteli, M. (British Journal of Healthcare and Medical Research, 2022)
Objective: The family needs of parents with children who have been diagnosed with Intellectual Disability (ID), have received attention in outcome research. The purpose of this study was to investigate the family needs of parents who have children with intellectual disability and examine their relationship with their demographic characteristics. Method: The research involved 134 parents of children have been diagnosed with ID and responded to the questionnaire through a structured interview. Τhe relationship between variables of interest and participants’ demographic characteristics was also analyzed. Results: The analysis of our collected data showed that parents expressed needs for more information, social support, and counseling services. In terms of demographic variables it was found that parents with younger children reported a small number of needs for social support and counseling services compared to parents of older children. In addition older parents reported more needs compared to younger parents.